A review on rice yellowing: Physicochemical properties, affecting factors, and mechanism. (15th February 2022) - Liu, Yuqian; Shad, Zeinab Mohammadi; Strappe, Padraig; Xu, Longhua; Zhang, Fengjiao; Chen, Yilun; Li, Dapeng
Highlights: The environmental factors, temperature and moisture on rice yellowing are dominant. The yellowing is mainly related to heat stress induced by heaping heat or respiration of grain. Yellowing is the collective result of primary and secondary metabolism. The upregulation of flavonoids is the direct cause of rice yellowing. Aeration and cooling are needed to reduce the rice yellowing during storage. Abstract: Yellowing is a critical issue that reduces quality and commodity value of rice. This article presents an overview on rice yellowing and the mechanism of rice yellowing was addressed as the emphasis. The change of physicochemical and nutritive properties in yellowed rice depends on the exposure temperature and time, as well as rice cultivar. The temperature and moisture on rice yellowing were dominant. There is no consensus on the relationship between microorganisms and rice yellowing. The occurrence of yellowing is mainly associated with heat stress induced by heaping heat or respiration of grain, and the yellowing is the collective result of primary and secondary metabolism. The upregulation of flavonoids is the direct cause of rice yellowing, which can be used as metabolic markers of rice yellowing. The Maillard reaction also contributes to yellowing during storage. Aeration and cooling are recommended to lessen the occurring of rice yellowing during commercial storage.